(3JaSjQ LRA Yes - (3eLghds ((3Ndjd Hf GdMGL QeVGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; HSe GdSjO GdcQje GdeYjf hcQeg YGe Ydi GdNdGjb CLeYjf dgPg GdShQ CQHYI CSeGA Ye jJSGAdhf hGdfHC hGdJSGDd hGdeYUQGJ hgd cdgG ecjI hYOO BjGJgG CQHYhf YfO GdHUQjjf CQHY hCQHYhf YfO GdHGbjfs
(3BNQgG (B:s
(3Ke bQC bd gh Gddg CMO hGdeYhPJjf Ke eSM HgeG hLgg hQCSg hSGjQ LSOg hbGd ef GSJYGP HGddg HGdYehPJjf eG Hbj TjA EdG bGd Gddge CYP efj hGddg CYdes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eMeO UGOb GdbGVjs
Keywords: (3GdJaSjQ hYdhe GdbQBfs